2022
DOI: 10.1007/s00424-022-02688-6
|View full text |Cite
|
Sign up to set email alerts
|

Tissue chaperoning—the expanded functions of fetuin-A beyond inhibition of systemic calcification

Abstract: Traditionally, fetuin-A embodies the prototype anti-calcification protein in the blood, preventing cardiovascular calcification. Low serum fetuin-A is generally associated with mineralization dysbalance and enhanced mortality in end stage renal disease. Recent evidence indicates that fetuin-A is a crucial factor moderating tissue inflammation and fibrosis, as well as a systemic indicator of acute inflammatory disease. Here, the expanded function of fetuin-A is discussed in the context of mineralization and inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 137 publications
(174 reference statements)
0
13
0
1
Order By: Relevance
“…Accordingly, we showed increased asialofetuin-A in neuroinflammation. The third mechanism refers to fetuin-A consumption during inhibition of dystrophic calcification attesting to its general role in tissue chaperoning (67,68). Inflammation causes cell damage with release of calcium and phosphate from damaged cells that promotes dystopic calcification while simultaneous energy depletion leads to diminished formation of pyrophosphate (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we showed increased asialofetuin-A in neuroinflammation. The third mechanism refers to fetuin-A consumption during inhibition of dystrophic calcification attesting to its general role in tissue chaperoning (67,68). Inflammation causes cell damage with release of calcium and phosphate from damaged cells that promotes dystopic calcification while simultaneous energy depletion leads to diminished formation of pyrophosphate (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…The fetuin-B structure allowed modeling of the complete structure of fetuin-A, which was later confirmed by AlphaFold2 21 . This novel fetuin-A model suggested that the hitherto undefined intrinsically unfolded C-terminal region should also occupy an important role in protein-mineral binding apart from the amino-terminal cystatin-like domain identified earlier 9 , 19 , 22 because it harbors several more putative Ser/Thr phosphorylation sites. This is in line with the current understanding of the role of intrinsically disordered proteins in biomineralization 23 .…”
Section: Introductionmentioning
confidence: 89%
“…Accordingly, we showed increased asialofetuin-A in neuroinflammation. The third mechanism refers to fetuin-A consumption during inhibition of dystrophic calcification attesting to its general role in tissue chaperoning [66,67]. Inflammation causes cell damage with release of calcium and phosphate from damaged cells that promotes dystopic calcification while simultaneous energy depletion leads to diminished formation of pyrophosphate [68,69].…”
Section: Plos Onementioning
confidence: 99%